Local Therapy of Acute Nasopharyngitis in Children - Ye.I. Yulish; B.I. Krivuschev (Zaslavsky O.Yu., 2013)
The paper presents data on the etiology, pathogenesis and clinical manifestations of acute nasopharyngitis in children. Methods of local treatment of the diseases using combined preparation with anti-inflammatory, decongestive and analgesiс action were considered and pathogenetically proved.